Serum biomarkers and postherpetic neuralgia in herpes zoster patients with immunocompetent - Liu, Huili; Yuan, Yanrong; Wang, Jun; Zhang, Yan; Yan, Yongxing (Frontiers in Neurology, 2025)
BackgroundPostherpetic neuralgia (PHN) typically occurs in immunocompromised patients. However, there is a lack of prospective studies involving large samples of immunocompetent individuals. A prospective study was conducted to ascertain the association between serum levels of various markers and the occurrence of PHN in acute herpes zoster (HZ) patients with immunocompetent.MethodsA total of 887 acute HZ patients with immunocompetent who were admitted to Hangzhou Third People’s Hospital between April 2021 and December 2023 were selected. Peripheral venous blood at their initial visit was collected and the levels of various serum markers were detected. According to whether PHN occurred or not during follow-up, the participants were divided into PHN group and non-PHN group. Multivariate logistic regression analysis was used to screen the influencing factors of PHN.ResultsTwo hundred and seventeen cases (24.5%) developed PHN. Compared with the non-PHN group, age, numerical rating scale (NRS) scores, levels of C reactive protein (CRP) and homocysteine (HCY) in PHN group were significantly increased (p < 0.01), while CD3+ (p < 0.05), CD4+ (p < 0.01), CD4+/CD8+ ratios (p < 0.05), albumin levels (p < 0.01), and albumin/globulin (A/G) ratios (p < 0.05) were significantly decreased. Multivariate logistic regression analysis showed that age, NRS scores, levels of CRP, and HCY were independent risk factors for PHN among acute HZ patients with immunocompetent. ROC curve analysis showed that the sensitivity and specificity of combined with age, NRS scores, CRP and HCY levels in predicting PHN were 68.4 and 74.1%, respectively.ConclusionAge and the severity of pain at the time of onset were also the risk factors for PHN in acute HZ patients with immunocompetent. The levels of serum CRP and HCY as potential biomarkers may have certain reference value for predicting the occurrence of PHN in acute HZ patients with immunocompetent.